IMPLIKASI KAWASAN WISATA TERHADAP PEREKONOMIAN DESA PUJON KIDUL - Raden, Mochammad Faza Fisilmi; Ajeng Kartika Galuh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to determine the methods used by BUMDes Sumber Sejahtera to improve the economy of the community in Pujon Kidul Village by looking at the unemployment rate, income, and type of work owned by the community. This research uses qualitative methods with data collection through interviews and documentation. The results of the study explain that the tourist area, namely Cafe Sawah, has an impact on village funds in the allocation of funds, provides employment for youth in the village, and has a positive impact on bad habits, namely drunkenness, gambling, and others. It can be said that the tourist area in Pujon Kidul Village, especially Cafe Sawah, has a majorimpact on the existing economy and socio-culture.